INTERPERSONAL MEANING NEGOTIATION IN THE TEACHER-STUDENT VERBAL INTERACTION - Yuliati, Yuliati (Language Circle: Journal of Language and Literature, 2016)
This study aims to reveal the role relationship among the teacher and the students of SMAN 4 Semarang Year XII and the way the teacher negotiate her interpersonal meaning to the students. The design of the research was a discourse analysis concerning on the analysis of mood suggested by Susan Eggins. A transcript of the teacher and students interaction was taken as the main source of data. I analyzed the data by using Mood Analysis suggested by Eggins.The results showed that most of the utterances produced by the teacher were in the form of command which means that the authority of the teacher was dominant. Besides, the teacher also tried to be equal with the students by using some declarative and interrogative types of Mood. These made the students respond well but not really elaborated her/his responses. Familiarity in implementing Subject, Finite, and Modality was the main reason due to the problem of Interpersonal Meaning Negotiation. This leads me to suggest that in the foreign language (FL) context lexico-grammar cannot be taken for granted. FL learners need to notice the grammar and eventually acquire it. This can happen if the learning process encourages focus on form. This point should be the focus of teaching English as a Foreign Language.